GP286 Can follow up renal ultrasound replace DMSA for detection of parenchymal changes if first ultrasound post urinary tract infection in children is normal? an audit of national UTI guidelines of ireland. (June 2019) - Rizwan, Muhammad; Gibson, Louise; Moore, Micheal
Abstract : Background: Urinary tract infections (UTI) in Children can cause serious morbidity as well as Scarring of kidneys leading to renal impairment. To manage UTI in children and avoid the bad outcome, there are different guidelines for close follow up and management of these children. There were new Irish guidelines set up in 2017 regarding imaging of these children which suggested Renal ultrasound (US) at admission of clinically well children with UTI followed by the Renal US after 6 months instead of DMSA if the initial US is normal. Method: We gathered the data of all sick children under 16 years of age from January 2014-Dec 2016, who were diagnosed with Culture proven UTI and had Renal US at admission and DMSA or Renal US at follow up. We identified 70 (39 male- 55.7%, 31 females-44.3%) cases who had all the data available on Microbiology, Radiology and medical notes, and excluded all those who were either out of catchment area, who lost follow up appointments, or whose report was not traced properly. In 70 children admitted there 32 (45.7%) who had repeat US along with DMSA. The reports were verified by Expert Pediatric Radiologist. Results: We found 62 (88.5%) normal initial US (Normal parenchyma), who had normal DMSA and repeat US (24 cases). There were 8 (11.5%) children who had abnormal initial US (parenchymal changes), which were confirmed by DMSA and repeat US (8 cases). Conclusion: Renal US could be a potential alternative of DMSA in children with UTI if the initial US has been reported normal if the scans are reported by Pediatric radiologist/Special interest in pediatric radiology. The renal US is cost and time effective, and in this way, we can avoid extra costs, day admissions and family anxiety related to the procedure.